2010 IEEE International Conference on Data Mining Workshops 2010
DOI: 10.1109/icdmw.2010.27
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Chinese Online Video Recommendations by Using Virtual Ratings Predicted by Review Sentiment Classification

Abstract: Abstract-In this paper we aim to resolve the recommendation problem by using the virtual ratings in online environments when user rating information is not available. As a matter of fact, in most of current websites especially the Chinese video-sharing ones, the traditional pure rating based collaborative filtering recommender methods are not fully qualified due to the sparsity of rating data. Motivated by our prior work on the investigation of user reviews that broadly appear in such sites, we hence propose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Figure 3 shows that the accuracy of the dataset C has the best accuracy values among the three existing datasets, amounting to 76.81%. In accordance with what is disclosed in the previous research (Zhang, Weishi, Ding, Chen, & Li, 2010) that the dataset C which has a balance composition of positive and negative data will result in a better classification since avoiding bias or deflection of weight word with a high number of occurrences in the negative data only or positive data only.…”
Section: ) Accuracy Analysis With Different Composition Positive Andsupporting
confidence: 64%
See 1 more Smart Citation
“…Figure 3 shows that the accuracy of the dataset C has the best accuracy values among the three existing datasets, amounting to 76.81%. In accordance with what is disclosed in the previous research (Zhang, Weishi, Ding, Chen, & Li, 2010) that the dataset C which has a balance composition of positive and negative data will result in a better classification since avoiding bias or deflection of weight word with a high number of occurrences in the negative data only or positive data only.…”
Section: ) Accuracy Analysis With Different Composition Positive Andsupporting
confidence: 64%
“…In research (Zhang, Weishi, Ding, Chen, & Li, 2010), it is said that the composition of the positive and negative of data need to be balanced to avoid any bias or weight deflection with a high number of occurrences in negative data only or positive data only. Therefore this test done to prove whether the situation also applies to the data of this research.…”
Section: ) Testing Dataset Scenario With Parameter Of Different Compmentioning
confidence: 99%
“…Similarly, Jakob et al [9] identified and clustered movie topics using movie reviews and a ratings matrix to recommend movies based on the prediction of user-topic similarity. Zhang et al [10], obtained good results in online video recommendation with a framework that extracts a like/dislike rating from textual reviews and comments to minimize data sparsity.…”
Section: Related Workmentioning
confidence: 99%
“…Existing work [3,4] reports that measuring the similarity of users using the sentiment of their text reviews, instead of ratings, improves the accuracy of user-kNN. However, we argue that a sentiment-based approach does not fully address the similarity reflection problem since the reasons behind a sentiment of a review remain unexploited.…”
Section: Introductionmentioning
confidence: 99%